Calibration of Hydrus-3D model for drip irrigation on stratified soil for intensive agriculture (sand covered soil) - A.J. Zapata-Sierra; J. Roldán-Cañas; R. Reyes-Requena; M.F. Moreno-Pérez (Ingeniería del Agua)
The development of the wet bulb under drip irrigation in sand covered soils presents a different behavior from that observed under homogeneous soils. The presence of a very active crop also imposes a series of variations that have not been fully characterized. The aim of this work is to present the data acquisition methodology and the necessary precautions to obtain a model that accurately defines the evolution of moisture in wet bulbs generated in sanded soils characteristic of intensive horticultural crops. The procedure for collecting and processing moisture data in stratified soils has been defined. The soil and permeability curve has been adjusted experimentally for each material. It has been proved that the Hydrus-3D model can reproduce the behavior of a sand covered soils and it has been possible to verify that the predictions are adequate to what has been observed in the field.